Review of Teaching Materials on Islamic Education Subjects for Higher Education: Case Studies in Indonesia - Pramesti Wulandari; Asrowi Asrowi; Djono Djono (Teknodika, 2022)
This research article aims to determine whether the development of teaching materials can positively impact and improve students' soft skills during the learning process. This qualitative research used the literature study method. Based on the explanation, the development of teaching material is closely related to learning planning. Teaching materials have become one of the components in the learning process, in which the design must follow the learning principles. Teaching materials also need to include instructions on how to learn, competencies to be achieved, lesson content, practice questions, work instructions, and assessments. Moreover, various teaching materials have been developed in Islamic Education subjects for higher education to help achieve the planned learning objectives in its development. Some developments of these teaching materials include Augmented Reality (AR), Islamic glossary applications, infographics, and animated infographics, analyzed in this article. These various developments of teaching materials are creative and innovative. Utilizing these technologies needs to be studied more deeply to produce effective teaching materials that can keep up with the times and improve students' soft skills.